Unraveling RubisCO Form I and Form II Regulation in an Uncultured Organism from a Deep-Sea Hydrothermal Vent via Metagenomic and Mutagenesis Studies - Böhnke, Stefanie; Perner, Mirjam (Frontiers in Microbiology, 2017)
Ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO) catalyzes the first major step of carbon fixation in the Calvin-Benson-Bassham (CBB) cycle. This autotrophic CO2 fixation cycle accounts for almost all the assimilated carbon on Earth. Due to the primary role that RubisCO plays in autotrophic carbon fixation, it is important to understand how its gene expression is regulated and the enzyme is activated. Since the majority of all microorganisms are currently not culturable, we used a metagenomic approach to identify genes and enzymes associated with RubisCO expression. The investigated metagenomic DNA fragment originates from the deep-sea hydrothermal vent field Nibelungen at 8°18′ S along the Mid-Atlantic Ridge. It is 13,046 bp and resembles genes from Thiomicrospira crunogena. The fragment encodes nine open reading frames (ORFs) which include two types of RubisCO, form I (CbbL/S) and form II (CbbM), two LysR transcriptional regulators (LysR1 and LysR2), two von Willebrand factor type A (CbbO-m and CbbO-1), and two AAA+ ATPases (CbbQ-m and CbbQ-1), expected to function as RubisCO activating enzymes. In silico analyses uncovered several putative LysR binding sites and promoter structures. Functions of some of these DNA motifs were experimentally confirmed. For example, according to mobility shift assays LysR1’s binding ability to the intergenic region of lysR1 and cbbL appears to be intensified when CbbL or LysR2 are present. Binding of LysR2 upstream of cbbM appears to be intensified if CbbM is present. Our study suggests that CbbQ-m and CbbO-m activate CbbL and that LysR1 and LysR2 proteins promote CbbQ-m/CbbO-m expression. CbbO-1 seems to activate CbbM and CbbM itself appears to contribute to intensifying LysR’s binding ability and thus its own transcriptional regulation. CbbM furthermore appears to impair cbbL expression. A model summarizes the findings and predicts putative interactions of the different proteins influencing RubisCO gene regulation and expression.